Odpowiedzi

2010-01-06T15:45:35+01:00
X/5-(3x-1)/3=4
3x/15-(15x-5)/15=4
(-12x-5)/15=4 /*15
-180x-5=4
180x=1
x=1/180

3(2x-4)<-(3-8x)
6x-8<8x-3
-2x<5
x>2,5

x należy do (2,5;plus nieskończoność)

3x-y=14
4x+3y=-3

y=3x-14
4x+3(3x-14)=-3

y=3x-14
4x+9x-42=-3

y=3x-14
13x=39

y=3x-14
x=3

y=9-14
x=3

y=-3
x=3
2010-01-06T15:50:25+01:00
C)3x-y=14 b)6x-12<-3+8x

4x+3y=-3 no i najpierw na osi

9x-3y=42 napiszesz -3+8x apotem to drugie
4x +3y=-3

13x=39 /:13 c)x/5=3x-1/3-4 dalej nie wiem
x=3

3x-y=14
3*3-y=14
y=-5

x=3
y=-5
2010-01-06T15:53:35+01:00
3(2x-4)<-(3-8x)

6x-12<-3+8x
6x-8x<-13+12
-2x<-1|:(-2)
x>0,5


3x-y=14|*3
4x+3y=-3

9x-3y=42
4x+3y=-3

13x=39|:13
x=3

4x+3y=-3
4*3+3y=-3
3y=-3-12
3y=-15|:3
y=-5